Morality and global justice : justifications and applications - Boylan, Michael, 1952- (Boulder, CO : Westview Press, 2011)
"Boylan makes a daring effort to take on the broad scope of global ethics in a manageable and comprehensive way. His introduction of the worldview imperatives in this context is imaginative and offers a way of engaging students while holding them accountable for their views."---Robert Paul Churchill, George Washington University --
"Morality and Global Justice meets the challenge of combining traditional ethics and moral theory with contemporary global concerns ... An excellent introduction for undergraduates and an engaging review for more advanced scholars."---Naomi Zack, University of Oregon --
In this concise, single-authored text, renowned scholar and professor Michael Boylan examines the moral justifications underlying crucial global justice issues and provides readers with the analytical tools to approach those issues critically. Introductory chapters establish a thorough but accessible foundation in theory and moral justification, and subsequent chapters apply those concepts to major areas of global concern. Each chapter includes Critical Applied Reasoning Exercises perfect for class discussions or writing assignments, as well as key terms for easy reference and review. The appendix, "How to Get Involved," suggests practical ways to put ethical principles to work. --
An anthology of original essays, The Morality and Global Justice Reader (ISBN: 978-0-8133-4433-1) is also available as a complementary or a standalone text. --Book Jacket.
The way people think about ethics and social/political philosophy -- The personal, shared-community, and extended-community worldview imperatives -- The foundation of global justice -- Human rights -- Culture and religion -- Justice, the state, and the world -- Poverty -- Public health -- Race, gender, and sexual orientation -- Democracy, and social and political dialogue -- Globalization -- The environment -- War and terrorism -- Immigrants and refugees.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Ethics, Modern; Globalization; Electronic books